Corporate Social Responsibility Practices Amid Political and Economic Transformation in Europe - Carataș, Maria Alina (Technium Social Sciences Journal, 2023)
Corporate social responsibility (CSR) has evolved over time, influenced by political, social, and economic changes, leading to a growing recognition of the importance of addressing social and environmental issues. Many companies now incorporate sustainability and social responsibility into their business strategies, but the role of CSR can vary across regions. The COVID-19 pandemic has emphasized the need for businesses to prioritize social and environmental issues. Methodology used secondary data analysis for emphasizing CSR practices of companies and CSR initiatives that proved to be a façade for corporate greenwashing. With this research the author intends to raise awareness over the social and environmental problems that should be seen as a matter of concern for individuals and organizations of all kind. The role of CSR in sustainable development is complex and multifaceted, and ongoing efforts are required to promote responsible business practices.